Rancang Bangun Smart Home System Pada Rumah Yang Terintegrasi Smartphone - Syaiful Bahri; Harry Pratama Figna; Ryan Dhika Priyatna; Ade Evi Fatimah (Indonesian Journal of Education And Computer Science, 2023)
In the 4.0 revolution era, technological developments are developing very fast. The security system is also growing, so that it can be implemented in various needs. One of them is a smart home system that can be monitored without limits using a smartphone. Currently CCTV is one of the security tools that are widely used at home, office, and others. There are also many CCTVs available that are digital, so the images are clearer and can be connected directly to the internet. The internet used also does not require a connection that is too fast but must be stable. Based on the results of the research that has been done, the home security system can use digital CCTV connected to the internet. CCTV that is connected to the internet can be monitored using a smartphone anytime and anywhere. The storage capacity used is 32 Gb and can store recordings for 9 days non-stop. The disadvantage of this system is that if the internet is unstable, playback will be interrupted, because the playback system used is directly accessed from CCTV